2021
DOI: 10.1002/admi.202100041
|View full text |Cite
|
Sign up to set email alerts
|

Hollow CeO2@Co2N Nanosheets Derived from Co‐ZIF‐L for Boosting the Oxygen Evolution Reaction

Abstract: Rational design of highly active electrocatalysts for the oxygen evolution reaction (OER) is critical to improving overall electrochemical water splitting efficiency. This study suggests hollow CeO2@Co2N nanosheets synthesized using Co‐ZIF‐L as a precursor, followed by a hydrothermal reaction and a nitridation process as very attractive OER catalysts. The increased activity is supposed to be due to nitridation and strong electronic interaction between CeO2 and Co2N that contribute to the formation of active Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Additionally, Schuhmann and coworkers synthesized CeO 2 @Co 2 N hollow nanosheets through a solvothermal process followed by subsequent nitridation process. 91 For the synthesis of metal phosphides, sodium hypophosphite (NaH 2 PO 2 ) is usually used during the phosphorization. For example, a hybrid nanoarray structure of V-CoP@a-CeO 2 integrated into CC (V-CoP@a-CeO 2 NRA/CC) was synthesized via a three-step process, including the hydrothermal reaction, phosphorization, and electrodeposition.…”
Section: Tmpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Schuhmann and coworkers synthesized CeO 2 @Co 2 N hollow nanosheets through a solvothermal process followed by subsequent nitridation process. 91 For the synthesis of metal phosphides, sodium hypophosphite (NaH 2 PO 2 ) is usually used during the phosphorization. For example, a hybrid nanoarray structure of V-CoP@a-CeO 2 integrated into CC (V-CoP@a-CeO 2 NRA/CC) was synthesized via a three-step process, including the hydrothermal reaction, phosphorization, and electrodeposition.…”
Section: Tmpsmentioning
confidence: 99%
“…Then, the charge density of Co sites can be enriched by some electron transfers from CeO 2 to Co 3 O 4 , which decrease the adsorption energy between Co active sites and OER intermediates, and thus improve the OER catalytic activity of Co 4 N-CeO 2 /GP. Schuhmann and coworkers developed hollow CeO 2 @Co 2 N nanosheets with better catalytic performance than unmodefied Co 2 N. They demonstrated that the nitridation and strong electronic interaction between CeO 2 and Co 2 Nfacilitate the formation of active CoOOH phase, which increased the activity 91. Besides, Shanmugam and coworkers prepared the heterostructure of Co-CeO 2 /N-CNR and demonstrated its excellent OER performance 109.…”
mentioning
confidence: 99%
“…34-0394), while the peaks for Co . 20 In the O 1s spectrum (Figure 5f), the peaks at 529.4, 530, 531.6, and 532.6 eV, are attributed to Ce−O, Co−O, oxygen defects, and absorbed O, respectively. 37,38 After the OER, the peak of the oxygen vacancy is much stronger than the other peaks, and the peak of the Co−O bond is also significantly enhanced, even stronger than that of the Ce−O bond, which further confirms the formation of CoOOH.…”
Section: Resultsmentioning
confidence: 99%
“…18,19 For example, Schuhmann and his collaborators have confirmed that the in situ generated CoOOH transformed from Co 2 N can accelerate the reaction kinetics for the OER. 20 However, insufficient adsorption energies toward reaction intermediates (O*, OH*, HOO*, etc.) are still issues that hinder the application of transition metal nitrides in the OER under alkaline conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In a word, the deposition of CeO 2 nanoparticles on Co 0.4 Ni 1.6 P leads to charge redistribution at the interface and the generation of abundant oxygen vacancies, which is believed to give rise to better OER performance of Co 0.4 Ni 1.6 P-CeO 2 . 57 In the P 2p region (Fig. 3f ), the peaks located at 129.4 and 130.3 eV correspond to P 2p 3/2 and P 2p 1/2 , respectively, while the peak at 134.0 eV is attributed to the oxidized P specie in Co 0.4 Ni 1.6 P, as a result of air contact.…”
Section: Paper Dalton Transactionsmentioning
confidence: 97%